Problems of Ensuring the Competitiveness of a Chinese Company in International Sales Markets - Junjian Lu; Robert Voskerichyan (Communications of International Proceedings, 2021)
The Chinese government has a great influence on the activities of national companies, regulating their activities. In the foreign and domestic markets, the PRC government provides preferential terms and provides all-round support to Chinese companies in their competition with Western corporations in gaining and maintaining positions in the world market. It is government assistance that can help strengthen the positions of Chinese companies in world markets and increase their competitiveness. China's accession to the WTO has provided Chinese companies with broader prospects for development in the global market. However, there are political, economic, cultural and legislative differences between China and other countries, which can become an obstacle to the development of Chinese companies in these countries. Meanwhile, there are still few world-class Chinese companies, the scale of their activities is small, and there are not enough factors of influence on the development of Chinese companies. The global economic crisis has reduced the export and investment activity of Chinese companies in the world market. The article expresses an attempt to analyze the factors of development of Chinese companies, search for ways to solve the current export problems of Chinese companies and increase their influence on the world market. The current global economic crisis has a negative impact on the increase in trade and the variety of types of investment cooperation between countries. Therefore, it is necessary to develop and implement optimal foreign economic mechanisms for Chinese companies. The article consistently studies the issues of the concept of competitiveness in international business, analyzes the company in the international market and identifies problems, which made it possible to highlight the main factors on which the company should build its competitiveness. The purpose of the article is to study the problems of ensuring the competitiveness of a Chinese company in international sales markets and to propose a strategy for the development of its competitiveness.
Keywords: International competitiveness; China; global trends; innovation; high-tech products; priorities for economic development; the effectiveness of strategic development; economic potential; globalization